Numerical methods and failure mechanisms of ferrofluid seals in centrifugal pumps - Li, Wangxu; Li, Hongliang; Li, Zhenggui; Han, Wei; Li, Rennian; Zhang, Yue (International Journal of Agricultural and Biological Engineering, 2026)
Ferrofluid seals are considered a next-generation sealing technology for hydraulic machinery due to their outstanding performance. However, experiments and engineering applications have revealed issues with seal failure, the mechanisms of which remain poorly understood. This study focuses on centrifugal pumps, employing numerical simulations to analyze the hydrodynamic characteristics and pressure pulsations in the sealing clearance. A coupling interface between the three-dimensional fluid machinery numerical results and two-dimensional ferrofluid seal numerical results was established to investigate the effects of mean and pulsating pressures on the ferrofluid interface morphology and the mechanisms of seal failure. The results indicate that the rotation of the centrifugal pump shaft induces forced vortices in the sealing clearance. Influenced by the clearance structure, these forced vortices generate free vortices with similar flow patterns. The vortex motion is identified as the primary factor causing pressure pulsations in the sealing clearance, with an amplitude of approximately 0.18 MPa due to scale limitations. Compared to the morphology of ferrofluid seals under mean pressure, pulsating flow does not cause partial detachment of the ferrofluid but accelerates the rupture process of the ferrofluid sealing ring. Under the critical pressure of the ferrofluid sealing ring, pulsating pressure causes significant damage within 0.8 s. This study concludes that the stability and failure of ferrofluid seals in centrifugal pumps are strongly governed by vortex-induced pressure fluctuations and the interaction between magnetic field distribution and flow dynamics. The designed four-level ferrofluid sealing device can effectively withstand peak pressure pulsations, demonstrating reliable sealing performance. These findings provide critical insights for optimizing ferrofluid seal designs and can guide the development of more reliable sealing technologies in high-speed hydraulic machinery, improving operational safety and efficiency. Keywords: hydraulic machinery, ferrofluid seal, multi-field coupling, failure mechanism DOI: 10.25165/j.ijabe.20261902.10146 Citation: Li W X, Li H L, Li Z G, Han W, Li R N, Zhang Y. Numerical methods and failure mechanisms of ferrofluid seals in centrifugal pumps. Int J Agric & Biol Eng, 2026; 19(2): 183–192.